Pulse shaping for broadband photoassociation of cold molecules - Friedman, M (2010)
The development of the field of the science of ultra-cold matter has opened some exciting possibilities in exploring the quantum-mechanical processes which dominate matter interactions at the sub-microscopic scale. Although methods of cooling atoms are well established, molecular cooling is made difficult by molecules’ additional vibrational and rotational degrees of freedom. It was the goal of the research in this work to approach molecular cooling indirectly, by using broadband shaped-pulse photoassociation for the generation of tightly bound ultracold Rb2 molecules. The experiments towards this goal conducted by our group included a pumpdecay experiment to observe the generation of ground state singlet or triplet molecules. However, attempts to observe an increase in ground state population have been unsuccessful. A pump-probe study of wavepacket dynamics in the 5s+5p electronic state was conducted in order to determine the appropriate timing for the application of an additional pulse to dump population into the ground state. Although the attempt to observe wavepacket oscillations has been unsuccessful, pump-probe studies have yielded the observation of loosely bound excited state molecules as a result of the photoassociation pulse. These results are promising as a first stage in a fully coherent pump-dump approach to stabilisation into the lowest vibrational ground state. This thesis will provide an introduction and overview to the concerns involved in addressing the problem of molecular cooling and generation. Experimental techniques will be discussed including pulsed laser systems, optical parametric amplifi- cation, and the presentation of an original design for pulse shaping with an acoustooptic modulator. The emphasis of these discussions will be on the principles and operating procedures required for the use of these devices as home-built systems. The thesis will conclude with the results of pump-probe experiments utilising the pulse shaper as a spectral cutting device.